2001
DOI: 10.1074/jbc.m102249200
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Bacterial Endosymbiont to the Biosynthesis of Pyrimidine Nucleotides in the Deep-sea Tube Worm Riftia pachyptila

Abstract: The deep-sea tube worm Riftia pachyptila (Vestimentifera) from hydrothermal vents lives in an intimate symbiosis with a sulfur-oxidizing bacterium. That involves specific interactions and obligatory metabolic exchanges between the two organisms. In this work, we analyzed the contribution of the two partners to the biosynthesis of pyrimidine nucleotides through both the "de novo" and "salvage" pathways. The first three enzymes of the de novo pathway, carbamyl-phosphate synthetase, aspartate transcarbamylase, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 47 publications
2
29
1
Order By: Relevance
“…It was previously reported that the carbamoylphosphate syn-thetase specific of the pyrimidine pathway (CPSase-P) 1 is absent in all of the worm tissues and is present only in the bacteria (17). In contrast, the carbamoylphosphate synthetase specific of the arginine biosynthetic pathway (CPSase-A) was found in all of the tissues of the worm (25).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…It was previously reported that the carbamoylphosphate syn-thetase specific of the pyrimidine pathway (CPSase-P) 1 is absent in all of the worm tissues and is present only in the bacteria (17). In contrast, the carbamoylphosphate synthetase specific of the arginine biosynthetic pathway (CPSase-A) was found in all of the tissues of the worm (25).…”
mentioning
confidence: 89%
“…Although the bacterial symbiont was shown to be able to reduce nitrate to nitrite (17,23,24), the mechanisms by which the worm assimilates and metabolizes nitrogen from its inorganic sources are much less well documented. However, ammonia assimilatory enzymes such as glutamine synthetase and glutamate dehydrogenase were found to be present in both the bacterial symbiont and the host (17,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this study presents the first demonstration of the requirement for a nucleoside-salvaging enzyme in bacterium-host interactions, though previous studies have suggested the importance of nucleoside salvaging to intracellular microbes during host interactions (4,7,15,22,23,29). Our data further suggest that, unless Tdk has an as-yet-unidentified alternative substrate, dT or dU is present in both the nematode and insect environments.…”
Section: Vol 71 2005mentioning
confidence: 55%
“…unusual multiple reaction has been purified in a homogenous state. The CAD is a dimeric enzyme which requires as a cofactor [7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%